Stvb-i, a Rice Gene Conferring Durable Resistance to Rice stripe virus, Protects Plant Growth From Heat Stress - Hayano-Saito, Yuriko; Hayashi, Keiko (Frontiers in Plant Science, 2020)
Disease resistance is affected by temperature. A rice gene, Stvb-i, is known to have conferred sustained resistance to Rice stripe virus (RSV) despite global warming. Stvb-i protects plants from growth stunting caused by RSV. The underlying resistance mechanism is unclear. Here, Stvb-i showed stable RSV resistance for 20 years in laboratory experiments. This gene encodes a protein distinct from well-studied plant disease-resistance proteins. It has a domain homologous to the histidine kinase/heat-shock protein 90-like ATPase superfamily. Rice has three paralogous genes including Stvb-i. The genes are expressed mainly in meristematic tissues. In the initial period after viral inoculation, RSV multiplication enhanced Stvb-i, whereas Stvb-i suppressed RSV multiplication. Stvb-i silencing inhibited plant growth regardless of viral infection, and silencing of the other paralogous gene that located closely to Stvb-i caused morphological abnormalities. The results suggested that the Stvb-i and its paralogs are related to plant development; especially, Stvb-i supports meristem growth, resulting in plant growth stabilizing. Growth stunting in the Stvb-i–silenced plants was more severe under repetitive heat stress, suggesting that Stvb-i contributed to the attenuation of heat damage in plant development. The symptoms of RSV infection (chlorosis, wilting, stunting, fewer tillers, and defective panicles) were similar to those of heat damage, suggesting that RSV multiplication induces heat-like stress in meristematic cells. Our findings suggest that the mechanism of meristem growth protection conferred by Stvb-i allows plants to withstand both heat stress and RSV multiplication. The suppression of RSV multiplication by the Stvb-i function in meristems results in durable resistance.